PENERAPAN E-LEARNING BERBASIS SCHOOLOGY PADA PEMBELAJARAN MATEMATIKA SISWA KELAS X SMA NEGERI 2 LUBUKLINGGAU - Zulfasal Sabilillah; Sukasno S; Drajat Friansah (JOURNAL of MATHEMATICS SCIENCE and EDUCATION, 2022)
This study entitled "Application of Schoology-based E-learning in Mathematics Learning of Class X Students of SMA Negeri 2 Lubuklinggau Academic Year 2020/2021. This study aims to determine the completeness of student learning outcomes after learning with Schoology-based E-learning is applied. This type of research used quasi-experimental. The population is all class X SMA Negeri 2 Lubuklinggau academic year 2020/2021 and the sample is class X IIS 3 which is taken randomly. The data was collected by means of a five-question essay form test technique. The collected data were analyzed using t-test at the significant level Î± = 0.05. Based on the results of data analysis, it can be concluded that the mathematics learning outcomes of class X IIS 3 SMA Negeri 2 Lubuklinggau after implementing Schoology-based E-learning are significantly complete. The average student learning outcomes were 75.04 and the percentage of students who completed reached 69,57%.